2016
DOI: 10.1002/jmor.20611
|View full text |Cite
|
Sign up to set email alerts
|

Exocrine glands of Lepeophtheirus salmonis (Copepoda: Caligidae): Distribution, developmental appearance, and site of secretion

Abstract: Exocrine glands of blood-feeding parasitic copepods are believed to be important in host immune response modulation and inhibition of host blood coagulation, but also in the production of substances for integument lubrication and antifouling. In this study, we aimed to characterize the distribution of different types of salmon louse (Lepeophtheirus salmonis) exocrine glands and their site of secretion. The developmental appearance of each gland type was mapped and genes specifically expressed by glands were id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 74 publications
2
40
1
Order By: Relevance
“…It has been hypothesised that astacins have digestive and anticoagulation roles, also inactivating prey/host vasoactive peptides [76,81] to maintain hostparasite relationships [82][83][84][85]. However, sea lice astacin is expressed in tegument glands associated with probable roles in lubrication of integument as opposed to feeding [86]. Therefore, the presence of these proteases in Argulus SEPs may be associated with functional roles in haematophagy, but as the feeding activity is similar to L. salmonis, they may also be involved in preventing drag when infecting moving fish.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been hypothesised that astacins have digestive and anticoagulation roles, also inactivating prey/host vasoactive peptides [76,81] to maintain hostparasite relationships [82][83][84][85]. However, sea lice astacin is expressed in tegument glands associated with probable roles in lubrication of integument as opposed to feeding [86]. Therefore, the presence of these proteases in Argulus SEPs may be associated with functional roles in haematophagy, but as the feeding activity is similar to L. salmonis, they may also be involved in preventing drag when infecting moving fish.…”
Section: Discussionmentioning
confidence: 99%
“…It has been hypothesised that to enable long term host contact and feeding, Argulus spp., like other ectoparasitic arthropods such as ticks and salmon lice (Lepeophtheirus salmonis (Krøyer, 1837)), must secrete a range of pharmacologically active components. These components have been suggested to be produced in the parasite's spinal, proboscis and labial glands and to be delivered through the preoral spine and the mouth tube to facilitate blood-feeding [7,8]. Argulus spp.…”
Section: Introductionmentioning
confidence: 99%
“…salmonis have highlighted the importance of secretions produced by a group of tegumental glands and labial glands to parasite virulence [22]. The similarity of the mode of parasitism expressed by Argulus spp.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…These glands, which comprise five large gland cells on each side of the body, were observed to be closely associated with the labium, and thus here it is suggested that these glands be termed the "labial glands". Recently, Øvergård et al [22] found that sea lice, L. salmonis, have two labial glands, each made of two large secretory units connected to storage reservoirs accumulating the glandular products before secretion…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation